Fotossíntese e eficiência do uso da água em vinte espécies lenhosas tropicais sob condições de campo em um reflorestamento utilizando espécies de mata - Ferreira, Leonnardo Lopes (Universidade Federal de São Carlos, 2003)
Leaf gas exchange characteristics were evaluated in 20 woody species of differing successional status, ranging from pioneer species to non-pioneers (late successional species) in a Brazilian forest ecosystem. The principal aim of this work was to point out the correspondence of leaf gas exchange parameters and each ecological successional group of plant species. Light saturated photosynthetic rate was different both on leaf area (PNA) or on dry mass (PNM) basis between two successional groups. PNA and PNM were higher in pioneer species and lower in non-pioneer species. Variation among species was 3-fold (from 7 to 23 µmol m-2 s-1) for PNA, and 5-fold (from 50 to 275 µmol kg-2 s-1) for PNM. The highest PNA (23 µmol m-2 s-1) and PNM (275 µmol kg-2 s-1) values were recorded in the pioneer Croton urucurana, while the lowest PNA (7 µmol m-2 s-1) and PNM (50 µmol kg-2 s-1) values were recorded in the putative late successional species Aspidosperma cylindrocarpon. The sub-stomatal CO2 concentration values (Ci) was also significantly different between pioneer and non pioneer species, but a considerable overlap was recorded between successional groups about leaf-atmosphere water vapor exchange such as stomatal conductance (gs) and transpiratory (E) rates. However, the pioneer C. urucurana showed again the highest gs and E values. Mass-based photosynthetic rate was highly correlated with specific leaf mass (SLM) in both pioneer and non-pioneer species (r=-0.75 and -0.90, respectively). The highest values of instantaneous transpiratory efficiency (ITE) and intrinsic water use efficiency (iWUE) were also observed in the pioneer species when compared with the non-pioneer species. The results suggest that tropical early successional species have greater ITE and iWUE than later successional species both conditioned by higher photosynthetic capacity values. Therefore, the carbon assimilation parameters by themselves (PNA, PNM and Ci) or associated with leaf-atmosphere water vapor gas exchange were more suitable to separate both studied groups than single gs or E. Os parâmetros estudados, quando considerados através de uma análise multivariada foram efetivos para separar em um espaço bidimensional as espécies pioneiras das não-pioneiras. Multivariate principal components analysis (PCA) was useful to separate in a two-dimensional space the pioneer and non-pioneers species using gas exchange and SLM parameters.
Keywords: Fotossíntese; Ecofisiologia vegetal; Trocas gasosas; Sucessão florestal; CIENCIAS BIOLOGICAS::ECOLOGIA